A Method for Fast Generating the VIE-MoM Matrix with the SWG Functions - Shu-Wen Chen; Hou-Xing Zhou; Wei-Dong Li; Guang Hua; Wei Hong (International Journal of Antennas and Propagation)
A method for fast generating the VIE-MoM matrix with the SWG functions is proposed. This method makes the integrals representing the shared data independent of any quadratures and hence can ensure both the efficiency and accuracy. In the VIE-MoM, the time cost of filling the VIE-MoM matrix is prominent especially for an electrically large object. With the proposed method, the time cost of filling the VIE-MoM matrix can be reduced by about 85% compared with the traditional basis-basis matching method. Numerical examples are provided to demonstrate the efficiency and accuracy of the proposed method.